KOMPETENSI GURU MENYAJIKAN MODUL SESUAI PASSION SISWA DALAM PENDIDIKAN ABAD 21 - Messi, Messi; Cuan, Bayu; Saputra, Eko Agus (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
In the era of technological developments that are increasingly developing in the 21st century, modules used in learning do not always use conventional modules such as paper-based modules. Today's teachers must be able to present subject matter in the form of modules that can be accessed online by students. The method in this study uses a qualitative descriptive research method. This study provides an overview of the teacher must be able to present the module according to the students' passion in 21st century education. The research was conducted in the State MA 3 of Palembang City and Purwadadi Musi Rawas Public High School. Data collection techniques used in this study were observation, interviews, and documentation. The results of this study are that not all teachers present modules in each lesson that are in accordance with the passion of students in education in the 21st century, in general the two schools teachers state that indeed in each subject that has been taught as well as presents the module but only teachers who I want to make the modules of some other teachers still use the available textbooks, based on Teacher's competency in the Industrial Revolution Era the teacher must be able to present modules according to the students' passion in 21st century education but with rapid technological development so that teachers must learn to follow the flow of globalization so that teachers can make presentations of modules that are compatible with the Passion of students in 21st century education.